Nanofluid Development Using Silver Nanoparticles and Organic-Luminescent Molecules for Solar-Thermal and Hybrid Photovoltaic-Thermal Applications - James Walshe; Pauraic Mc Carron; Conor McLoughlin; Sarah McCormack; John Doran; George Amarandei (Nanomaterials, 2020)
Exploiting solar energy using photo-thermal (PT) and/or hybridised photovoltaic/thermal (PVT) systems can represent a viable alternative to the growing demand for renewable energy. For large-scale implementation, such systems require thermal fluids able to enhance the combined conversion efficiency achievable by controlling the ‘thermal’ and ‘electrical’ components of the solar spectrum. Nanofluids are typically employed for these purposes and they should exhibit high heat-transfer capabilities and optical properties tuned towards the peak performance spectral window of the photovoltaic (PV) component. In this work, novel nanofluids, composed of highly luminescent organic molecules and Ag nanoparticles dispersed within a base fluid, were tested for PT and PVT applications. These nanofluids were designed to mimic the behaviour of luminescent down-shifting molecules while offering enhanced thermo-physical characteristics over the host base fluid. The nanofluids’ conversion efficiency was evaluated under a standard AM1.5G weighted solar spectrum. The results revealed that the Ag nanoparticles’ inclusion in the composite fluid has the potential to improve the total solar energy conversion. The nanoparticles’ presence minimizes the losses in the electrical power component of the PVT systems as the thermal conversion increases. The enhanced performances recorded suggest that these nanofluids could represent suitable candidates for solar energy conversion applications.